2018
DOI: 10.1021/acsaem.8b00586
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Impedance Analysis of Oxygen Exchange on Growing La0.6Sr0.4CoO3−δ Thin Films

Abstract: The further development of solid oxide fuel and electrolysis cells (SOFC/SOEC) strongly relies on research activities dealing with electrode materials. Recent studies showed that under operating conditions many perovskite-type oxide electrodes are prone to changes of their surface composition, leading to severe changes of their electrochemical performance. This results in a large scatter of data in literature and complicates comparison of materials. Moreover, little information is available on the potentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 68 publications
2
37
1
Order By: Relevance
“…In an earlier study using IPLD it was already discussed that about 2-3 nm LSC are required to cover the Pt current collectors to an extent that true LSC properties are measured. 19 In accordance with this study, the rst measured spectrum aer 2 nm (100 pulses) includes three clearly distinguishable features ( Fig. 5).…”
Section: Impedance Spectroscopy On Lsc Thin Lms During Growthsupporting
confidence: 86%
See 3 more Smart Citations
“…In an earlier study using IPLD it was already discussed that about 2-3 nm LSC are required to cover the Pt current collectors to an extent that true LSC properties are measured. 19 In accordance with this study, the rst measured spectrum aer 2 nm (100 pulses) includes three clearly distinguishable features ( Fig. 5).…”
Section: Impedance Spectroscopy On Lsc Thin Lms During Growthsupporting
confidence: 86%
“…Details of the method are described elsewhere. 19 At the beginning a corundum plate is placed directly on the platinum heating wires. To contact the counter electrode, a platinum sheet is placed on top and xed by a corundum frame with an opening.…”
Section: In Situ Impedance Spectroscopy During Pld (Ipld)mentioning
confidence: 99%
See 2 more Smart Citations
“…The authors proposed that the increased ORR activity results from the increased oxygen vacancies in epitaxial LSC64 films due to the large tensile strain of high-quality films. Employing in situ impedance spectroscopy during thin film growth, Rupp et al [97] also showed an enhancement in the oxygen surface exchange kinetics of tensile-strained epitaxial LSC64 films on (001)-oriented La 0.95 Sr 0.05 Ga 0.95 Mg 0.05 O 3−δ substrates compared to unstrained films on yttria-stabilized zirconia (YSZ) substrates. Similar to the results by Lee et al [96], the authors also found the same trend of enhanced oxygen surface exchange kinetics as film thickness decreases in epitaxial LSC64 films but they interpreted that this trend may be attributed to the capability of in-situ measurement as the films never exposed to any thermal cycling such as cooling from PLD preparation temperature or heating for impedance measurements.…”
Section: Cobaltitesmentioning
confidence: 99%